The effect of feeding with soybean on serum levels of TSH, T3 and T4 in male mice - Modaresi Mehrdad; Khorrami Hormat; Asadi-Samani Majid (Shahrekord University of Medical Sciences, 2014)
Introduction: Soybean possesses isoflavones and might, therefore, cause problem in thyroid hormone synthesis. The purpose of this study was to study the effect of soybean on serum levels of Thyroid stimulating hormone (TSH), Triiodothyronine (T3), and Thyroxine (T4) in male mice. Methods: In this experimental study, 24 Balb/C male mice were randomly assigned to three groups of eight including control or base diet-fed group and treatment groups 1 and 2 receiving respectively 30% and 50% soybean-containing diet. After nine weeks, the blood sample was taken from the animals' heart and serum levels of TSH, T3, and T4 were measured. The data were analyzed by SPSS software using one-way ANOVA and Duncan's test. Results: In 50% soybean group, a significant decrease was observed in T4 serum level compared to the control group (p<0.05). On the other hand, this hormone level non-significantly decreased in the group fed by 30% soybean compared to the control group (p<0.05). TSH serum level increased significantly in 30% soybean group compared to the control group (p<0.05). But, serum level of T3 was not significantly different between 30% or 50% soybean groups and control group (p>0.05). Conclusion: In view of the findings, it is estimated that the effect of addition of soybean into meal on thyroid function is dose-dependent, so that the diet containing 30% and 50% soybean might cause increased TSH release in thyrotrope cells and hence variation in pituitary-thyroid axis function.